„Zwijanie” ponowoczesności. O nowym realizmie Maurizia Ferrarisa - Zawadzki, Andrzej (Przestrzenie Teorii, 2020)
This article presents the views of Maurizio Ferraris, one of today’s best-known Italian middle-generation philosophers. Since the end of the 1990s, he has been constructing a concept he calls new realism. It is a critique of postmodernism defined in the broad sense, which, in Ferraris’ view, is characterised by the primacy of interpretation over facts, epistemology over ontology, conceptual schemes over reality. Ferraris assumes the possibility of strictly separating the two cognitive activities: the primary determination of facts and their secondary interpretation. Ferraris’ realist views are also expressed in his aesthetics and the concept of social document, founded on the notion of trace understood in the material sense. The author also attempts to critique Ferraris’ views on his understanding of realism and interpretation.